Estudio Socioeconómico de los Sistemas de Producción alrededor del Cultivo de Chocho en la Parroquia Juan Montalvo, Barrio Yugsiloma, Provincia de Cotopaxi 2017-2018. - Sandoval Ponce, Christian Josué (2018)
The project “Socioeconomic study of production systems around the cultivation of chocho in the parish Juan Montalvo, Yugsiloma neighborhood, Cotopaxi province” has as specific aims to determine the Social, Economic, Environmental and productive structure in the margin of sustainability taking as reference ranges of 1 which means very sustainable; 0,75 which means more or less sustainable; 0,50 as sustainable and 0,25 not sustainable for the following, the study area where the research was carried out was defined, for which the survey was designed and applied through a collect application that served as a guide for the survey field in which it was addressed to the producers of the neighborhood. Once the collection of the survey was analyzed the information collected and the information collected (data) was elaborated with the tabulated data consequently it disseminates the information that will be acquired as knowledge about analyzed results for deducing the investigated components of the community. The universe under study is made up of 21 families of small producers which, for optimization of resources it worked with the universe in total. For the achievement of the aims it used non-experimental research and documentary bibliography, the methods used were the descriptive and the hypothetical deductive; diagnostic criteria used for the elaboration of the surveys as general characteristics of the UPA, long-cycle crops, pests of long-cycle crops, if it has orchards, perception of pests, if it has animals, labor and organization of agricultural work and finally evaluation of expenses with this research information was obtained. The alternative proposed for improving the production systems in the community would be required according it faces the problems such as the requirement of drinking water, more training in the agricultural area, marketing proposals, for the strengthening of the community. The results obtained in the community of Yugsiloma of the social component resulted that it is sustainable with an average of 0,63 which is bigger than 0,50 while in the economic component resulted that it is sustainable with an average of 0,72 which is bigger than 0,50. On the other hand, the environmental component resulted that is sustainable with a range of 0.61 that is bigger than 0.50 and finally in the production component resulted that is sustainable with a range of 0,57 that is bigger than 0,50; the places where the agriculture is minimal and the excellent crop is the corn occupying the 75% percentage of the sector lands, being older adults who dedicate themselves to this activity, the profits of the harvests use it in education and the payment of credits related with the activities carried out, their income oscillates between 360 to 400 USD.